Environmental effects in the formation of contemporary groups of Santa Inês lambs - Koritiaki, Natália Albieri; Ribeiro, Edson Luis de Azambuja; Muniz, Carolina Amália Souza Dantas; Marestone, Bruna Silva; Constantino, Camila (Semina: Ciências Agrárias, 2019)
The objective of this work was to study the influence of environmental effects, sex of the lamb, type of birth, year of birth, birth season, julian birth date, and lambing weight on the weights and biometric measurements of Santa Inês lambs from birth to weaning (70 days of age), and to define the best-adjusted statistical model. Data on weights, heights, body lengths, and thoracic perimeters obtained at birth and close to 28 and 70 days of age from 270 lambs were used. Three analyses were carried out considering different models; one with isolated environmental factors, one with animals grouped into contemporaries according to lamb sex, type of birth, year of birth, and season of birth (GC1), and one with animals gathered in groups of contemporaries according to lamb sex, type of birth, year of birth, season of birth, and the julian date of birth (GC2). Environmental factors influenced a large proportion of body weights and measurements from birth to weaning; the main factors were type of birth and year of birth. The GC2 evaluations presented higher determination coefficients and lower values for Akaike information criteria. However, many observations were discarded; 114, 111, and 103 compared with those rejected by the GC1 analysis, which included two, three, and four observations at birth, 28 days of age, and at weaning, respectively. This may lead to the exclusion of animals with genetic potential.